A Multidisciplinary Synthesis of Artificial Intelligence in Literature and Business - Neupane, Dasarath; Mariam, Alesh (NPRC Journal of Multidisciplinary Research, 2025)
Background: The development of Artificial Intelligence (AI) in the corporate world has also existed in a historical setting of AI being portrayed in literature and films, whereas the two happen in parallel, hence leading to a remarkable divide between the ethical issues of the humanities field, which explore philosophical issues, and the efficiency-focused goals of the corporate world of business. Objectives: As an overview and analysis piece, there are essentially three objectives that can be defined for the paper: (1) to bring together and assess the ways by which literary stories have influenced the notion and risks of AI, and (2) to give an overview of the paradigms through which businesses conceptualize AI. Finally, (3) there are essentially areas where the preoccupations and concerns of literature have now materialized as issues that businesses face. Methods: The methodology that was adopted in this study involves integrating a multidisciplinary collection of literary works via a narrative review approach. The sources that have been utilized in this study include literary texts such as works by Shelley, Asimov, and Dick, texts of critical theory such as post-humanism theory, and peer-reviewed articles in business management. The sources were searched via an academic database based on keywords intersections literature, technology and business. Findings: Five key themes of intersection were uncovered in the literature: Autonomy and Control (“rogue AI” in literature versus the "black box" issue in business); Ethics and Responsibility (the Frankenstein Complex versus corporate accountability); Labor and Identity (threats to obsolescence versus workforce enhancement); Language and Creativity (human uniqueness versus commoditization via Large Language Models); and finally, Narrative Shift from Dystopian fear to Collaboration in both spheres. These findings clearly illustrate that the fears expressed in literature do not remain within the domain of fiction but anticipate current challenges faced in the corporate sphere. Conclusion: As reported by the news piece, to achieve positive change in the ethical and sustainable adoption of AI in society, it becomes imperative to fill the gap existing between the two cultures: those relating to STEM fields and those pertaining to the humanities. Where business success will be appraised for efficiency and profit, it needs to measure success by the extent to which technology will generate a future for every person to flourish. Novelty: This review offers a novel multidisciplinary synthesis that directly places foundational literary-philosophical frameworks in dialogue with contemporary business strategy and applications. It moves beyond parallel discussions to argue that humanistic wisdom provides an indispensable, practical toolkit for navigating the ethical complexities of AI in commerce, a perspective often absent in purely technical or economic analyses.